2022
DOI: 10.3389/fgeed.2022.854334
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Consumer Preferences Regarding Gene-Edited Food Products

Abstract: Innovations in food production and processing have largely remained “behind the scenes” for decades. The current nature of social media and calls for increased transparency regarding food results in a new landscape where consumer product demands are more important than ever, but are increasingly based on limited, or incorrect, information. One area where consumer awareness is rapidly emerging is the area of gene-edited food products. This article uses a consumer survey to gather perceptions regarding food safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A recent study reported that consumers’ reluctance to consume GE foods was associated with neophobic preferences. 34 Neophobia, which refers to a fear of novelty, may arise from a lack of knowledge or information about the technologies involved and can be addressed through increased consumer education. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that consumers’ reluctance to consume GE foods was associated with neophobic preferences. 34 Neophobia, which refers to a fear of novelty, may arise from a lack of knowledge or information about the technologies involved and can be addressed through increased consumer education. 35 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a Canadian report that highlighted trust in the Canadian food safety system as an important factor influencing consumer perceptions of GE foods. 34 Increasing knowledge about safety confirmation before market distribution may enhance transparency surrounding GE foods and contribute to increased acceptance. While previous studies have emphasized the importance of increasing knowledge, 9 , 38 the present study provides insights into the specific knowledge that needs to be understood to improve the acceptability of GE foods.…”
Section: Discussionmentioning
confidence: 99%
“…We measured participants' perceived risks of food irradiation using three items: one adapted from [11], one adapted from [76], and one adapted from [77]. The three items were: (1) eating irradiated food can increase the likelihood of contracting cancer; (2) eating irradiated food can damage human health; and (3) food irradiation can negatively impact the environment.…”
Section: Instrumentationmentioning
confidence: 99%
“…These off-targets can be overcome by the dimeric nuclease method, which is highly precise and specific (145). According to (147), low levels of knowledge about gene editing occur because information generated in scientific studies has not been communicated effectively to consumers (148).…”
Section: Genetic Engineering/transgenic Approachmentioning
confidence: 99%